The Role of Kiai Syakirun in Preaching through the Using of Wayang Kulit in Tipar, Rawalo, Banyumas Regency (1998-2016) - Dzikriyah, Istiqomatul; Fauji, Sidik (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2022)
The role of Kiai Syakirun in spreading Islam using the wayang kulit as media demonstrated a fairly exciting method. Every Wayang Kulit performance conducted by Kiai Syakirun conveyed meaningful messages, especially regarding religious, social, and cultural life. In his performance, every wayang movement showed a positive message. This spectacular performance lies because the Islamic values and practices used by Kiai Syakirun are more easily captured by the public. In this study, the authors used historical research methods consisting of heuristics, verification, interpretation, and historiography. The theory used in this research is the theory of cultural and religious relevance. The results of this study are in the process of preaching in Tipar Village, Kec. Rawalo, Kab. Banyumas, Kiai Syakirun using shadow puppet media. He recites Quranic verses echoed with songs and explain the wayang characters depicted in human life. Kiai Syakirun's role in spreading Islam in Tipar Village is very influential within his neighborhood. As Kiai Syakirun's influence gradually increased, inhabitants in his community abandoned their customs, such as worshiping trees and eating wild boars as side dishes. All their habits are abandoned and replaced by worship, praying and, reciting the Koran, eating by relying on natural products such as vegetables